BUKTI PENINGGALAN KERAJAAN HINDU BUDHA: IDENTIFIKASI CANDI MUARO JAMBI SEBAGAI BAHAN AJAR SEJARAH - Rizka Apriliani (Prabayaksa: Journal of History Education, 2025)
This study aims to identify and analyze the Muaro Jambi Temple as evidence of the Hindu-Buddhist Kingdom heritage and evaluate its potential as a history teaching material at the high school level. The study used a descriptive qualitative approach with data collection techniques through literature studies and in-depth interviews with history teachers. The results of the study indicate that the Muaro Jambi Temple Complex is the largest archaeological site in Southeast Asia with an area of approximately 12 km² which has approximately 80 temples. This site reflects the Hindu-Buddhist civilization that developed in the 7th to 14th centuries AD, with the characteristic architecture using red bricks and an orientation facing the Batanghari River. In the context of education, the Muaro Jambi Temple has been integrated into the history curriculum for grade X through Basic Competencies 3.6 and 4.6, with various contextual learning activities such as historical exploration, making temple distribution maps, and local history article projects. This study reveals that the use of historical sites as teaching materials can increase the relevance of history learning and strengthen students' understanding of the national cultural heritage. However, challenges still exist in terms of accessibility and more optimal integration into the national curriculum.